If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 138 * 3d = d Multiply 138 * 3 414d = d Solving 414d = d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-1d' to each side of the equation. 414d + -1d = d + -1d Combine like terms: 414d + -1d = 413d 413d = d + -1d Combine like terms: d + -1d = 0 413d = 0 Divide each side by '413'. d = 0 Simplifying d = 0
| 7x+10-6x=20 | | x+(x+30)=4000 | | 1x=1x+6 | | .33(x+3)+.17(x-6)=x+3 | | 5m-23=-28+6m | | 4(5-a)+2(3a+1)= | | .33(x+3)+.16(x-6)=x+3 | | ln(5x-3)=2 | | 138*3d= | | 9y+5y+y= | | W^2+5w-50=0 | | 4×3/4 | | 3(x-1)+3=13 | | 5x+6=5(x+7) | | 5x-25=26+2x | | 4×3/8 | | (8-3x)/(2√(4-x)) | | -10r=-40 | | 13-9x=26-16x | | 9=-(r-5)+1 | | x^2+4n+4=0 | | 6z=-117 | | 42+4y-11=12y-11-2y | | (2w-9)(w)=110 | | (5x+4)=0 | | 8x-27+5x+18=180 | | 22+3y-6=11y-9-3y | | 17+X=22.3 | | -2x+3=7x-5 | | 0=950x^5/2 | | 6x+-5=2x+3 | | (x+3)(x-2)=2x |